Effect of magnetizing voltage frequency on Barkhausen noise signal - Ahola, Oskari (2020)
Effect of magnetizing frequency on Barkhausen noise signal measurements in dynamic high frequency Barkhausen noise was studied. 100, 250, 500 and 1000 Hz magnetizing frequencies were used in the measurements for three different bearing race samples with several different Barkhausen noise sensors. Sampling rate was decreased and sensor surface velocity was increased linearly with the increasing magnetizing frequency. Measurements were successful with all of the used frequencies. However, the background noise was increased with the higher frequencies. Moving average filtering was used for some of the 1000 Hz measurements in order to decrease background noise. Using the moving average filter to 1000 Hz measurement data improved signal-to-noise ratio up to 205% compared to the original 1000 Hz measurement in some cases and 68% compared to the 100 Hz measurement in some cases. Background noise levels were decreased up to 280% in some cases.